Physalis floridana Cell Number Regulator1 encodes a cell membrane-anchored modulator of cell cycle and negatively controls fruit size - Li, Zhichao (Journal of experimental botany, 2015)
© The Author 2014. Published by Oxford University Press on behalf of the Society for Experimental Biology.